Are Common Sense Model constructs and self-efficacy simultaneously correlated with self-management behaviors and health outcomes: A systematic review. Issue 1 (January 2020) - Breland, Jessica Y; Wong, Jessie J; McAndrew, Lisa M
This systematic review answered two questions among adults with chronic conditions: When included in the same statistical model, are Common Sense Model constructs and self-efficacy both associated with (1) self-management behaviors and (2) health outcomes? We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and included 29 articles. When included in the same statistical model, Common Sense Model constructs and self-efficacy were both correlated with outcomes. Self-efficacy was more consistently associated with self-management behaviors, and Common Sense Model constructs were more consistently associated with health outcomes. Findings support the continued inclusion and integration of both frameworks to understand and/or improve chronic illness self-management and outcomes.